(untitled) (Jurnal Teknodik, 2018)
Games Book is one of the learning media used by teachers in teaching the learning materials to students through the game. The game is inserted into a book in which there is a variation of game that makes studentsfeel interested and follow it up. Games Book provides a new alternative in active and collaborative learning to increase reading interest and reading activities, especially on Indonesian Language subject in Primary School. Based on the conducted research in Grade Five of the Public Primary School Karamatjaya, Games Book media turned out provide a positive stimulus to the activity and reading interest of students, especially on the material elements of intrinsic story. Based on the collected data, qualitatively and quantitatively, the average influence of the treatmet utilizing games book media on the students’ reading interest before and after treatment, showing a significant increase, from averagely 62.24% to 90.81%. Referring to the research result, there is an increase of reading activity and interest of the students, the students become more critical, independent, and able to develop interaction and cooperation with other students Games Book merupakan salah satu media pembelajaran yang digunakan guru dalam mengajarkan materi pelajaran kepada siswa melalui permainan. Permainan terselip di dalam sebuah buku yang berisikan variasi permainan yang memungkinkan siswa tertarik dan mengikutinya. Games Book memberikan alternatif baru dalam membelajarkan siswa secara aktif dan kolaboratif untuk meningkatkan minat dan aktivitas baca, khususnya pada mata pelajaran Bahasa Indonesia di Sekolah Dasar. Berdasarkan penelitian di kelas V SD Negeri Karamatjaya, media Games Book ternyata memberikan rangsangan positif terhadap aktivitas dan minat baca siswa terutama pada materi pelajaran tentang unsur unsur intrinsik cerita. Berdasarkan data yang dikumpulkan, kualitatif dan kuantitatif, didapatkan data rata-rata pengaruh perlakuan pemanfaatan media games book terhadap minat dan aktivitas baca siswa secara signifikan, yakni dari rata-rata 62,24% menjadi 90,81%. Merujuk pada data tersebut, tampaklah adanya peningkatan aktivitas dan minat baca, siswa lebih kritis, mandiri, dan mampu membangun interaksi dan kerjasama dengan siswa lain.